Emansipasi Sebagai Tata Bahasa Telaah Filsafat Moral Axel Honneth tentang Multikulturalisme - Alexander Seran (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2013)
This article is concerned to show Axel Honneth’s philosophical approach that explains the struggle for the establishment of relations of mutual recognition, as a precondition for self-realization. Like G.W.F.Hegel, G.H. Mead, and many feminist proponents, Honneth stresses the importance of social relationships to the development and maintenance of a person’s identity. Honneth develops a framework for interpreting social struggles based on common values. The moral philosophy of Honneth can be applied in interpreting Pancasila as universal principles that must be reflected in positive-lawmaking. Therefore the constitution and rules or regulations that are based on the constitution can be amended to meet society’s needs and demands.